PENGUNGKAPAN DIRI DAN KEPUASAN PERNIKAHAN PADA INDIVIDU YANG MENIKAH MELALUI PROSES TA’ARUF - Fitri Sakinah; Melok Roro Kinanth (UIN Sunan Kalijaga, 2018)
The aim of this study was to examine the contribution of self disclosure toward marital satisfaction among individuals who married through ta'aruf process. Using the quantitative approach and associative design, the data in this study were collected from 88 participants through The Self-Disclosure Scale (Billetter, 2002) and ENRICH Marital Satisfaction (Fowers and Olson, 1993). Data were analyzed by simple regression analysis and revealed that the contribution of self disclosure to maritalsatisfaction were 8,7%. This research explores the way of self-disclosure in order to help individuals to achieve a satisfying marriage life.Keywords: Self Disclosure, Marital Satisfaction, Ta’aruf.